2016
DOI: 10.3389/fpsyg.2016.00727
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying Associations between Childhood Adversity, Social Support, Behavioral Factors, and Mental Health, Health, and Well-Being in Adulthood: A Population-Based Study

Abstract: Previous studies have shown that socio-demographic factors, childhood socioeconomic status (CSES), childhood traumatic experiences (CTEs), social support and behavioral factors are associated with health and well-being in adulthood. However, the relative importance of these factors for mental health, health, and well-being has not been studied. Moreover, the mechanisms by which CTEs affect mental health, health, and well-being in adulthood are not clear. Using data from a representative sample (n = 12,981) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
143
5
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(167 citation statements)
references
References 149 publications
(194 reference statements)
15
143
5
4
Order By: Relevance
“…Other mechanisms are also likely to play a role in the associations of these specific MFF childhood adversities with PTSD, including habitual use of maladaptive emotion regulation strategies (such as rumination) and low social support, each of which is associated with child maltreatment and parent psychopathology as well as risk for PTSD. 1,41,54-56 …”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms are also likely to play a role in the associations of these specific MFF childhood adversities with PTSD, including habitual use of maladaptive emotion regulation strategies (such as rumination) and low social support, each of which is associated with child maltreatment and parent psychopathology as well as risk for PTSD. 1,41,54-56 …”
Section: Discussionmentioning
confidence: 99%
“…We used the difference-in-coefficients method with IOW63 64 to assess mediation. An OR scale is not suitable for assessing mediation, as it tends to overestimate the direct effect and underestimate the indirect effect, particularly when the outcome is not rare (eg, proportion of unhealthy >5%) 15. This bias in direct/indirect effects increases with prevalence of the outcome; therefore, we recommend estimating relative risks (RRs), even when the outcome is rare.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that children from low socioeconomic backgrounds are at a higher risk of experiencing psychological abuse and physical abuse in childhood (Dubowitz et al, 1987; Whipple and Webster-Stratton, 1991; Belsky, 1993; Fergusson and Lynskey, 1997; Garbarino, 1999; Hussey et al, 2006; Currie and Spatz Widom, 2010; Schilling and Christian, 2014; Romens et al, 2015). In turn, psychological abuse and physical abuse in childhood may have a long-term impact on mental health (anxiety and depression), general health (health-related quality of life), and subjective well-being (Sheikh et al, 2016a). In this way, CSES may influence mental health, general health, and well-being in adulthood, partly through psychological abuse and physical abuse in childhood.…”
Section: Background and Theoretical Considerationsmentioning
confidence: 99%
“…Some previous studies have focused on only one childhood adversity (Kessler et al, 1997; Fuller-Thomson et al, 2012), but children exposed to one type of adversity are likely to be exposed to other types of adversities in childhood (Sheikh et al, 2016a). Since different adversities may be correlated and co-occur in the same individuals, we aim to address the question of whether there is an independent and unique effect of CSES, psychological abuse, and physical abuse in childhood on mental health, general health, and well-being in adulthood, a question which has been rarely addressed in previous studies (Sheikh et al, 2016a). …”
Section: Background and Theoretical Considerationsmentioning
confidence: 99%